2013
DOI: 10.1186/1471-2334-13-611
|View full text |Cite
|
Sign up to set email alerts
|

Performance of commercial dengue NS1 ELISA and molecular analysis of NS1 gene of dengue viruses obtained during surveillance in Indonesia

Abstract: BackgroundEarly diagnosis of dengue infection is crucial for better management of the disease. Diagnostic tests based on the detection of dengue virus (DENV) Non Structural Protein 1 (NS1) antigen are commercially available with different sensitivities and specificities observed in various settings. Dengue is endemic in Indonesia and clinicians are increasingly using the NS1 detection for dengue confirmation. This study described the performance of Panbio Dengue Early NS1 and IgM Capture ELISA assays for dengu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 40 publications
5
42
0
1
Order By: Relevance
“…These low numbers were in accordance with previous studies describing the low sensitivity of NS1 detection in Indonesia [49,50]. …”
Section: Discussionsupporting
confidence: 93%
“…These low numbers were in accordance with previous studies describing the low sensitivity of NS1 detection in Indonesia [49,50]. …”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, NS1 antigen was detected in serum samples of DENV-4 patients, but not in urine samples. Using the present ELISA method, other investigators have demonstrated that the NS1 antigen-positive rate of serum samples from DENV-4 patients (19z) was lower than that of other DENV serotypes (DENV1, 67z; DENV-2, 68z; DENV-3, 69z) (30). Further studies using a higher number of urine samples obtained from DENV-4 patients are expected to address the discrepancies in NS1 antigen detection rates between serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies showed that these tests had lower sensitivity for the detection of DENV-4. Additionally, these commercial tests had decreased sensitivity in detecting secondary dengue infections, common in dengue endemic countries [3][4][5][6][7][8][9]. Commercially available NS1 antigen (Ag) tests manufactured by BioRad (Platelia) and Panbio (Dengue Early) both have low sensitivity to DENV-4 infections [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available NS1 antigen (Ag) tests manufactured by BioRad (Platelia) and Panbio (Dengue Early) both have low sensitivity to DENV-4 infections [8,[10][11][12]. Previous evaluations of Dengue Early test showed a sensitivity as low as 19% for DENV4 [6,8,[13][14][15]. Although the overall sensitivity of Platelia test was good however when comparing the sensitivities between all DENV serotypes, the BioRad test had the lowest sensitivity for DENV-4 (58.3%) [10].…”
Section: Introductionmentioning
confidence: 99%